Predicting ash deposit tendency in thermal utilization of biomass - Pakamon Pintana (2018)
© 2016, Chulalongkorn University 1. All rights reserved. In thermochemical utilization of biomass, ash produced during the process is a major problem that can result in decreased performance and increased in difficulty during operation. Preliminary assessment of potential ash related troubles prior to the use of a specific biomass is valuable, even if it is only a general guideline. In this work, tendency of ash slagging, fouling and agglomeration in thermal processing of biomass was evaluated. Reference peered reviewed data including mineral content and fusion temperature of selected biomass ash were used to calculate multiple indicators (base to acid ratio, slagging index, fouling index, agglomeration index, slag viscosity index, and ternary diagram of main biomass ash composition) adopted from coal research. Major ash forming elements (Fe, Ca, Mg, K, Na, Al, Si) were found to be of relevance to ash melting and deposit behavior. For conventional biomass available locally, woody biomass (wood and wood sawdust) may be combusted without slagging or fouling problem, while non-woody biomasses (bark, husk, straw) are highly probable to experience some of these problems. The ash fusibility predictive models for woody and non-woody biomass were found to be effective. Mitigation can then be designed possibly via fuel blending to avoid or minimize the impact of biomass ash related trouble.